2001
DOI: 10.1385/jmn:17:3:351
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Carnosine, Homocarnosine and N-Acetyl-L-Histidine Hydrolytic Activities in Cultured Rat Macroglial Cells

Abstract: N-acetyl-L-histidine (NAH) and N-acetyl-L-aspartate (NAA) are representatives of two series of substances that are synthesized by neurons and other cells in the vertebrate central nervous system (CNS). Histidine containing homologs of NAH are beta-alanyl-L-histidine or carnosine (Carn) and gamma-aminobutyrl-L-histidine or homocarnosine (Hcarn). A homolog of NAA is N-acetylaspartylglutamate (NAAG). These substances belong to a unique group of osmolytes in that they are synthesized in cells that may not to be ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Whereas ASPA showed no activity against NAH, amidohydrolase I was active against NAA at 0.15 mmol/ g/h or about 6% of its activity against NAH. These two enzymes are associated with different glial cells in rat brain cell cultures, with ASPA highly expressed in oligodendrocytes and amidohydrolase I activity highly expressed in astrocytes [30]. NAH has previously been found to be present in rat brain [31], and in this investigation it was found that of all cells tested, only cultured rat neurons contained small quantities of NAH.…”
Section: Naa Metabolism In Normal Brainmentioning
confidence: 50%
See 1 more Smart Citation
“…Whereas ASPA showed no activity against NAH, amidohydrolase I was active against NAA at 0.15 mmol/ g/h or about 6% of its activity against NAH. These two enzymes are associated with different glial cells in rat brain cell cultures, with ASPA highly expressed in oligodendrocytes and amidohydrolase I activity highly expressed in astrocytes [30]. NAH has previously been found to be present in rat brain [31], and in this investigation it was found that of all cells tested, only cultured rat neurons contained small quantities of NAH.…”
Section: Naa Metabolism In Normal Brainmentioning
confidence: 50%
“…In CD, excretion of NAA by this alternate method ranges from 3 to 5 mmol/d, a value that represents the turnover of almost all brain synthesized NAA each day [8]. Another minor pathway for removal of some NAA from brain ECF in CD could be via astrocyte uptake and hydrolysis by amidohydrolase I [30]. In this article, except where specific metabolic sequences are involved, the terms NAA and its NAA-waterMe þ complex are used interchangeably since the anionic solute NAA cannot exist independently at the physiological pH of the brain.…”
Section: Naa Metabolism In CD Brainmentioning
confidence: 99%
“…In the dietary His supplementation studies [ 19 , 20 ], a therapeutic role for the essential amino acid His in synthesis of NAH and preventing lens cataract formation in teleost fish was reported. This observation may have relevance to homeotherms where NAH and the His dipeptides, Carn and Hcarn are present in cultured rat neurons [ 26 ] and Carn and Hcarn are important biomolecules in human brain and eye.…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with previous studies. In the mammalian brain, carnosine and homocarnosine, but not anserine, have been detected [96]. It is secreted from oligodendrocytes by the stimulation of glutamate [97].…”
Section: Carnosine In the Brainmentioning
confidence: 99%